Surgery induces neurocognitive disorder via neuroinflammation and glymphatic dysfunction in middle-aged mice with brain lymphatic drainage impairment - Zhu, Xiaoqiu; Lin, Jingrun; Yang, Pengfeng; Wu, Shaotao; Lin, Huijun; He, Wen; Lin, Daowei; Cao, Minghui (Frontiers in Neuroscience, 2024)
Background: Brain lymphatic drainage impairment is a prevalent characteristic in both aging and neurodegeneration. Surgery is more likely to induce excessive neuroinflammation and postoperative neurocognitive disorder (PND) among patients with aging and neurodegeneration. We hypothesized that surgical trauma may aggravate PND through preexisting cerebral lymphatic drainage impairment. However, there remains limited understanding about the role of surgery in changes of neurocognitive function in the populations with preoperative brain lymphatic drainage impairment. This study aims to expand our insight into surgery-induced glymphatic dysfunction, neuroinflammation and PND in middle-aged mice with preoperative brain lymphatic drainage impairment. Materials and methods: Deep cervical lymph nodes ligation (LdcLNs) was performed on middle-aged mice to establish preoperative brain lymphatic drainage impairment. A month later, laparotomy was performed on these mice with or without LdcLNs followed by analysis of brain neuroinflammation, glymphatic function, neuronal damage, and behavioral test. Results: LdcLNs disrupted meningeal lymphatic drainage. In middle-aged mice with LdcLNs, surgery exacerbated more serious glymphatic dysfunction accompanied by aggravation of A1 astrocytes activation and AQP4 depolarization. Furthermore, surgery caused neuronal damage via reducing expression of neuronal nuclei (NeuN), post-synaptic density protein 95 (PSD95) and synaptophysin (SYP), as well as impairment in exploratory behavior and spatial working memory in middle-aged mice with LdcLNs. Additionally, surgery induced neuroinflammation with elevated microglia activation and increased the levels of tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6, as well as activated more expression of HMGB1/TLR-4/NF-κB pathway in middle-aged mice with LdcLNs. Conclusion: Surgery exacerbates neuroinflammation and glymphatic dysfunction, ultimately resulting in neuronal damage and neurocognitive disorder in middle-aged mice with preoperative brain lymphatic drainage impairment. These results suggest that brain lymphatic drainage impairment may be a deteriorating factor in the progression of PND, and restoring its function may serve as a potential strategy against PND.